White blood cell count affects fetal fraction and test failure rates in noninvasive prenatal screening - Qiao, Longwei; Cao, XiaoJu; Tang, Haoyu; Yu, Zheng; Shi, Jingye; Xue, Ying; Wang, Ting; Liang, Yuting; Huang, Chao; Wang, Jiucun (Frontiers in Medicine, 2023)
Objective To investigate the effects of white blood cell (WBC) count on fetal fraction (FF), which is an essential quality control for obtaining reliable results, and on the rate of screen failures in noninvasive prenatal screening (NIPS). Methods NIPS, serum lipid and liver enzyme level measurements, and WBC count were performed for 4,281 pregnancies with male fetuses. After adjusting for confounders, including the maternal characteristics and alanine aminotransferase (ALT) levels, the effect of WBC count on FF and test failure rate was measured by linear and logistic regression analyses. Results FF was negatively associated with BMI, ALT, IVF conceptions, and WBC count and positively correlated with gestational age in the multivariate linear regression model. Moreover, WBC count was the most important factor affecting FF after BMI according to the standardization coefficient analysis. In the 4,281 pregnancy samples with male fetuses, FF decreased with WBC count from 11.45% at ≤8 to 9.02% at >12, and FF markedly decreased to 7.40% in pregnancies with a higher WBC count (>12) and higher BMI (≥25 kg/m2). Meanwhile, the test failure rates were significantly higher in the WBC count > 12 group (4.29%) than in the WBC count ≤ 8 group (0.89%). Notably, when the BMI of pregnancies with a WBC count of >12 was >25, the rate reached 7.53%. Subsequently, multivariate logistic regression analysis further confirmed that an increased BMI and WBC count were independently and significantly associated with the test failure rates. Conclusions An increased WBC count was associated with lower FF and higher test failure rates, suggesting that these important factors should be carefully considered during genetic counseling in pregnant women who decide to undergo blood collection or resampling.